Mountain social-ecological resilience requires transdisciplinarity with Indigenous and local worldviews - Ibarra, Jose Tomas; Caviedes, Julian; Marchant, Carla; Mathez-Stiefel, Sarah-Lan; Navarro-Manquilef, Silvia; Sarmiento, Fausto O. (My University, 2023)
Addressing the shocks of global crises requires that scientists, pol-icymakers, and Indigenous Peo-ples and Local Communities work together to enable communities to withstand and adapt to distur-bances. On the basis of our experi-ences in the Andes, we propose the '10-step cycle of transdisciplinarity' for designing projects to build social-ecologi cal resilience in mountains.
Keywords: andes; biocultural diversity; climate change; montology; public policy; social-ecological systems; sustainability